2019
DOI: 10.1589/jpts.31.878
|View full text |Cite
|
Sign up to set email alerts
|

Isometric knee muscle strength measurement using a belt-stabilized hand-held dynamometer and an isokinetic dynamometer with and without trunk fixation: investigation of agreement of measurement values and factors influencing measurement

Abstract: [Purpose] The purpose of this study was to examine the agreement between the values obtained by using a hand-held dynamometer with a belt (belt-HHD) and an isokinetic dynamometer (IKD) for the measurement of isometric knee flexion and extension muscle strength. We also studied the factors influencing the measurement. [Participants and Methods] Overall, 26 healthy young adults (16 males, 10 females) participated in the study; the mean age was 21 years. Knee flexion and extension muscle strength were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The values in this study were obtained from repeated measurements, and the reproducibility was confirmed by us and others. 29 30 48 Namely, an interclass correlation coefficient of test–retest reliability on the measurements of the sit-to-stand time was 0.996 (95% CI 0.988 to 0.999). Second, physical performance measures were not examined in patients with grip strength greater than the median.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The values in this study were obtained from repeated measurements, and the reproducibility was confirmed by us and others. 29 30 48 Namely, an interclass correlation coefficient of test–retest reliability on the measurements of the sit-to-stand time was 0.996 (95% CI 0.988 to 0.999). Second, physical performance measures were not examined in patients with grip strength greater than the median.…”
Section: Discussionmentioning
confidence: 93%
“…This method is new, portable, and simple, and was validated by comparing it with a conventional method using an isometric dynamometer. 29 Furthermore, the usefulness for patients with diabetes was confirmed and the details of the measurements were as described by Nomura et al 30 In brief, patients maintained an upright posture with the hip and knee joints bent at 90° in the end-sitting position. The sensor pad was applied on the anterior surface of the lower leg, which was 25 cm below the knee joint fissure.…”
Section: Physical Performance Measuresmentioning
confidence: 93%
“…On the other hand, from results of no significant difference and no correlation in the female was inferred that the difference with male of the maintenance capability of trunk stability to the material of peripheral fixation part of HHD and IKD (sensor pad or lower leg cuff) during measurement influenced the measurement value. Katoh et al 25) reported that knee extension strength value is high the belt-stabilized HHD than the modified IKD; not fixing the trunk etc. no touching floor, and by sitting on the mat table IKD.…”
Section: Discussionmentioning
confidence: 99%
“…To measure knee extension strength, the athlete was sitting at the edge of a treatment table and a belt was positioned at the proximal thighs. 27 The knees were bent to 90 o , and the HHD was placed at the anterior lower leg proximal to the ankle. 27 The examiner held the HHD in position by placing their elbows in their abdomen with their back against the wall to provide a more stable barrier (Figure 8).…”
Section: Muscle Strengthmentioning
confidence: 99%